FINANCIAL DEVELOPMENT AND ECONOMIC GROWTH - A COMPARATIVE ANALYSIS - Yay, Guelsuen; Oktayer, Asuman (INST ECONOMIC FORECASTING, 2009)
This paper investigates the relationship between financial development and economic growth for developed and developing countries comparatively. The impacts of both stock markets and banks on economic growth are examined by using a panel data set of 21 developing and 16 developed economies for the period 1975-2006. Generalized method of moments technique developed for dynamic panel is applied. While the results of the econometric evidence relevant to developing economies indicate that both stock markets and banks positively influence the economic growth, the results of econometric evidence relevant to developed economies indicate that only stock markets positively influences the economic growth.
Keywords: economic growth; stock markets; banks; financial markets; dynamic panel; PANEL-DATA; TECHNOLOGICAL CHOICE; LIBERALIZATION; TRADE; Business & Economics